Dietary quality and environmental footprint of health-care foodservice: a quantitative analysis using dietary indices and lifecycle assessment data - Pörtner, Lisa Maria; Schlenger, Leon; Gabrysch, Sabine; Lambrecht, Nathalie J (The lancet. Planetary health, 2025)
Background - Despite the key role of diets for individual and planetary health, the food offered in health-care institutions has received very limited attention to date. An assessment of the overall healthiness of foodservice in health-care institutions is missing from the literature, as is detailed information on its environmental footprint. This study aims to provide a comprehensive assessment of the healthiness, nutritional adequacy, and the environmental footprint of foodservice in a sample of German hospitals and nursing homes. - Methods - We investigated the dietary quality and environmental footprint of foodservice in two hospitals and three nursing homes in Germany (two in northern Germany, two in eastern Germany, and one in southern Germany). Average daily meals were derived from meal plans and recipes and analysed for dietary quality, using the Healthy Eating Index-2020; adherence to the Planetary Health Diet; and nutritional adequacy. The environmental footprint was analysed by allocating procured foods to 50 food groups and using an environmental database to estimate impacts on land use, greenhouse gas emissions, eutrophication, acidification, and water use. - Findings - Dietary quality was low, with institutions scoring 39-57 of 100 points on the Healthy Eating Index-2020. Adherence to the Planetary Health Diet was also low, reflected in Planetary Health Diet Index scores of 30-44 of 150. Most calories were from animal-source foods and unhealthy plant-based foods, with less than 20% of calories from wholesome plant-based foods. Meals were consistently high in saturated fat and salt, and low in fibre, while protein was insufficient in nursing homes. Micronutrient provision varied, with several B vitamins, vitamin C, potassium, and magnesium critically low in almost all institutions. Animal-source foods were responsible for three-quarters of the environmental impact, with meat alone contributing 38% of greenhouse gas emissions and 33-45% of other environmental impacts. About 60% of procured protein was from animal-source foods, while legumes made up less than 1% of procurement by weight. - Interpretation - Meals served in health-care institutions such as hospitals and nursing homes might compromise both short-term and long-term health of patients and residents and contribute unfavourably to the institutional environmental footprint. This study highlights the urgent need to regularly assess foodservice in health-care settings, align it with recommendations for healthy and sustainable diets, and improve nutritional care. - Funding - German Federal Environmental Foundation (Deutsche Bundesstiftung Umwelt).
Online verfügbar: 23. Juli 2025, Artikelversion: 5. August 2025
Gesehen am 19.01.2026